2014
DOI: 10.1063/1.4872464
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic characterization of 355 nm laser-crystallized silicon: Interplay of film thickness and laser fluence

Abstract: We present a detailed study of the laser crystallization of amorphous silicon thin films as a function of laser fluence and film thickness. Silicon films grown through plasma-enhanced chemical vapor deposition were subjected to a Q-switched, diode-pumped solid-state laser operating at 355 nm. The crystallinity, morphology, and optical and electronic properties of the films are characterized through transmission and reflectance spectroscopy, resistivity measurements, Raman spectroscopy, X-ray diffraction, atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…With these parameters, and with the beam approximated as rectangular, each point is scanned approximately 700 times by the laser. Further details of the laser setup and crystallization process can be found in a recent publication [13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With these parameters, and with the beam approximated as rectangular, each point is scanned approximately 700 times by the laser. Further details of the laser setup and crystallization process can be found in a recent publication [13].…”
Section: Methodsmentioning
confidence: 99%
“…Unique morphologies, such as high-aspect-ratio pillars or flat crystals, have also been observed as a result of the laser crystallization of a-Si films, where the specific type of morphology depends on details related to the laser and processing parameters [6,[9][10][11][12][13][14][15]. As the laser fluence is increased, the silicon melts and starts to flow in response to interfacial tension coupled with substrate interactions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The ability of excimer laser to crystallize a very thin layer of a-Si:H in the order of 100 nm becomes a limitation for photovoltaics, since films of the order 1 µm are necessary for light absorption [20]. Larger thickness means higher laser fluence needed for the crystallization [21]. It is concluded that it is not possible to convert a-Si:H films thicker than 300 nm completely to polycrystalline silicon without utilizing laser energy densities in excess of 200 mJ/cm 2 [22].…”
Section: Introductionmentioning
confidence: 99%